Evaluación de los niveles de concentración de metales pesados en las aguas del río motil de la provincia de otuzco. - Girón Estela, Teófilo Baltazar (2014)
This work was done with the porpose to evaluate the concentration levels of heavy metals in river waters Motil, employed by a fish farming, managed by the Fishery Regional Directorate of La Libertad in which is performed the breeding and rearing of trout, a hydrobiological resource which belogs to the variety "rainbow" (Oncorhynchus mykiss) intended for planting in different streams of the highlands of La Libertad region, as well as the consumption of residents of the area. Was quantified the concentration of heavy metals: arsenic, zinc, copper, mercury, lead and iron; and cyanide. Water samples were collected from four seasons called: In front of the town of Motil, Intake, Fish Farming Center and former cableway station. The study material was composed of 36 water samples taken during the months of October and December 2009 and July 2010 which were subjected to chemical analysis ICP- MS (Inductively Coupled Plasma – Spectrometry Mass). According to the results, the waters of the Motil river present heavy metals: arsenic, zinc, copper, iron, lead concentrations below the established MPLs DS-002-2008 MINAM Annex I for use in Class I and III ; mercury concentrations below 0.00323 mg/L. Cyanide concentrations in all parts were less than 0.01 mg /L.